Locating medical information during an infodemic: information seeking behavior and strategies of health-care workers in Germany - Holzmann-Littig, Christopher Werner Karl; Stadler, David; Popp, Maria; Kranke, Peter; Fichtner, Falke; Schmaderer, Christoph; Renders, Lutz; Braunisch, Matthias Christoph; Assali, Tarek; Platen, Louise; Wijnen-Meijer, Marjo; Lühnen, Julia; et al. (Healthcare, 2023)
COVID-19; infodemic; health-care workers; HCW; information strategies; emergency information